Physical Properties of Sputtered Germanium-Doped Indium Tin Oxide Films (ITO: Ge) Obtained at Low Deposition Temperature - S. J. Wen; G. Campet; J. P. Manaud (Active and Passive Electronic Components)
Undoped and Ge-doped ITO films (ITO: Ge) deposited at low temperature (70℃) have been studied. Although both samples have the same carrier concentration, a higher carrier mobility occurs for ITO: Ge. An evaluation of the relative position of the dopant associated energy states has been carried out.